Photon upconversion utilizing energy beyond the band gap of crystalline silicon with a hybrid TES-ADT/PbS quantum dots system12. Issue 18 (15th April 2019) - Nishimura, Naoyuki; Allardice, Jesse R.; Xiao, James; Gu, Qifei; Gray, Victor; Rao, Akshay
Abstract : Photon upconversion with an excitation of energy below the band gap of crystalline silicon was demonstrated with a hybrid system consisting of molecules based on a thiophene conjugated acene ( i.e., TES-ADT) and lead sulphide (PbS) quantum dots. Abstract : The recent introduction of inorganic semiconductor quantum dots (QDs) as triplet sensitizers for molecular semiconductors has led to significant interest in harvesting low energy photons, which can then be used for photon upconversion (PUC), via triplet–triplet annihilation (TTA). A key goal is the harvesting of photons from below the bandgap of crystalline silicon 1.12 eV (≈1100 nm) and their upconversion into the visible region. In practice, the systems demonstrated so far have been limited to harvesting photons with energies above 1.2 eV (≈1 μm), due to two reasons: firstly the need to use transmitter ligands which allow efficient energy harvesting from the QD but introduce an energy loss of larger than 200 meV in transmission from the QD to the annihilator, and secondly due to the use of molecules such as tetracene which cannot accept smaller energy than 1.2 eV. Here, we introduce a new strategy to overcome these difficulties by using a low energy triplet annihilator that also harvests excitations efficiently from QDs. Specifically, we show that 5, 11-bis(triethylsilylethynyl)anthradithiophene (TES-ADT, triplet energy of 1.08 eV: ca. 1150 nm) functions as a triplet annihilator (20% TTA efficiency) while also rapidly extracting triplet excitons from lead sulfide (PbS) QDs with a rate constant of k = ca. 2 × 10 −8 s −1 with an excitation at 1064 nm. This rate is consistent with an orbital overlap between TES-ADT and PbS QDs, which we propose is due to the thiophene group of TES-ADT, which enables a close association with the PbS surface, allowing this system to function both as annihilator and transmitter. Our results pave the way for the design of triplet annihilators that can closely associate with the QD surface and harvest low energy excitons with minute losses in energy during the TET process, with the ultimate goal of efficiently utilizing photon energy beyond the bandgap of crystalline silicon.